From meniscus formation to accelerated H− beam: coupling of 3D-PIC and ion-optics simulations. (1st December 2022) - Lindqvist, Max; den Harder, Niek; Revel, Adrien; Mochalskyy, Serhiy; Mimo, Alessandro; Nocentini, Riccardo; Minea, Tiberiu; Fantz, Ursel
Abstract: The ITER NBI is based on negative hydrogen ions extracted from caesiated ion sources. The 3D particle-in-cell Monte Carlo collision code Orsay negative ion extraction (ONIX) models the beamlet formation of negative ions in such sources where surface production plays an important role. A coupling scheme between ONIX and the ion-optics code ion beam simulator (IBSimu) has been developed and compared to other particle simulation approaches. This extends the computational domain such that the complete grid system can be included while only marginally increasing the computational cost. The properties of the accelerated ONIX beamlet are studied and compared to standalone IBSimu calculations, which are based on a simplified plasma model. The comparison provides insight about the effect of approximations made in ion-optics codes, which were also used to design the ITER NBI grid systems. ONIX volume and surface produced negative ions have a different angular distribution in the accelerated beamlet. The ONIX volume produced particles have a similar core divergence compared to standalone IBSimu calculations, but there is more halo in the IBSimu angular distribution. In the ONIX simulations, a Debye sheath is formed between the plasma and the grid, which repels negatively charged particles. The sheath decreases the extracted current density at the edge of the aperture for volume produced ions. Contrarily, surface produced particles are directly extracted near the edge of the aperture. Particles extracted near the edge of the aperture are highly divergent at the end of the grid system, independent of their initial angle. To summarize, the presence of the plasma sheath around the apertures in the plasma grid as calculated by ONIX decreases the halo from volume produced particles compared to standalone IBSimu.